Komodifikasi Kehidupan di Desa pada Akun Instagram @hidupdidesa_ - Wardani, Ayu; Misbah, Nuril Ashivah; Hayati, Kumala (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
The Instagram platform is a medium used to share information from its users. The information shared in each account has its own characteristics and goals. The @hidupdidesa_ account is one of the Instagram accounts that uses representations of village life as its hallmark. Natural life in the village with agricultural characteristics is the main thing displayed in every @hidupdidesa_ content. Purpose: This research aims to analyze the commodification of village life on the @hidupdidesa_ Instagram account through Roland Barthes semiotic analysis. Methods: : In dissecting the commodification used by the @hidupdidesa_ Instagram account, Roland Barthes' semiotic analysis method is used. Conclusion: Commodification is an effort used to create a commodity, which then leads to the desire for profit. The @hidupdidesa_ account on the Instagram platform makes the arena of village life a form of content commodification. In @hidupdidesa_ uploads, life in the village is represented as comfortable, fertile, beautiful, and far from urban modernization. Implications: Based on Roland Barthes analysis of signifiers and signs (semiotics), it is found that there are various messages about unusual rural life on @hidupdidesa_ Instagram content, where the messages constructed in rural life lead to the meaning of messages about sustainable life. The meaning of the sustainable life message is illustrated in the representation of cooking from scratch, Do It Yourself, and environmentally lifestyles.